The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Nanotechnology 2010
DOI: 10.1002/9783527628155.nanotech039
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Domain Wall Logic

Abstract: Magnetic domain wall logic technology is based upon controlling the magnetization processes in ferromagnetic nanowire circuits. Opposite magnetization directions in the nanowires are used to denote logical “1” and “0”. Switching between these two states is achieved by using applied magnetic fields to propagate magnetic domain walls through the nanowires. Nanowire junctions are used to perform various operations, including logical NOT, logical AND, signal fan‐out and signal cross‐over. A suitable combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
268
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(270 citation statements)
references
References 32 publications
2
268
0
Order By: Relevance
“…Commonly, Ni-Fe alloys are subjected to magnetic field during their exploitation (by the magnetic field of the Earth) and in the laboratory experiments too (up to 50 T). Small magnetic fields are used at annealing of soft magnetic materials for generating the predefined modification of the local atomic environment and nanoscale domain structures [1,3,5,6,22,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, Ni-Fe alloys are subjected to magnetic field during their exploitation (by the magnetic field of the Earth) and in the laboratory experiments too (up to 50 T). Small magnetic fields are used at annealing of soft magnetic materials for generating the predefined modification of the local atomic environment and nanoscale domain structures [1,3,5,6,22,23].…”
Section: Resultsmentioning
confidence: 99%
“…Also, it was revealed that the magnetic field can change the morphology of the ferritic (α-Fe-C solid solution) grains in Fe-C alloys [20] as well as both the morphology and the roughness of the electrodeposited layers of a pure nickel and Ni-Fe alloys depending on the applied magnetic-field direction [21]. In Permalloy-type alloys, which have recently obtained their promising applications in both solid-state magnetic random access memory (MRAM) technology and magnetic logic [22,23], the applied magnetic fields are commonly exploited to form or switch the predefined local magnetic structures, to control the movement of static (Bloch or Néel) domain walls, and so forth. For such bulk crystal alloys, the recent Monte Carlo modelling predicts, for instance, the increase of the order-disorder phase-transformation temperature [24] when the applied magnetic field increases.…”
Section: Introductionmentioning
confidence: 99%
“…Popular approaches include passing a spin current through the soft layer to generate a spin transfer torque [2][3][4][5][6][7] or spin orbit torque [8][9][10][11] or domain wall motion [12][13] . Other approaches involve using voltage controlled magnetic anisotropy 14 , magnetoelectric effects [15][16][17] , magnetoionic effects 18 and magnetoelastic effects [19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%
“…spin, shows promise for surpassing the development limits of CMOS logic. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Especially, due to the compatibility with conventional charge-based device, magnetic logic in magnetoelectronics arouses profound attentions. [5][6][7][8][9][10][11][12][13][14][15] Benefit from the extra dimension of spin, magnetic logic has the attractive features of reconfigurable logic operation and built-in non-volatile memory.…”
Section: Introductionmentioning
confidence: 99%